Socio-Educational Partnership as a Factor in Increasing the Efficiency of Preparing the Teaching Staff - Zelenko, Natalia Vasilyevna; Dyakova, Elena Anatolyevna; Zelenko, Grigoriy Nikolaevich; Rybakova, Anna Alexandrovna; Chanakaev, Giray Magomedzagidovich (Journal of History Culture and Art Research, 2017)
The article is devoted to actual problems of modernization of pedagogical education in view of educational priorities and demands from consumers of educational services. Based on the held experiment and generalized experience there were revealed the forms of the implementation of socio-educational partnership between the pedagogical institutions and the state and local governments, the educational establishments, the cultural and sports establishments, the public organizations. The most optimal forms of socio-educational partnership were considered the following: participation of employer’s representatives in correction of curriculum and teaching programs, direction of the course and diploma projects, final state attestation of graduates; running joint experimental researches; conducting joint scientific and entertaining activities; employment assistance. The study concludes that social-educational partnership facilitates the increase of quality of educational process and plays an important role in increasing the quality of training of the future teachers.